Differential Diagnosis of Pneumonia as a Complication of Nasal Liquorrhea in the Context of the COVID-19 Pandemic - E. V. Shelesko; O. E. Sharipov; N. A. Chernikova; O. N. Ershova; P. L. Kalinin; M. A. Kutin; D. V. Fomichev (SINAPS LLC, 2021)
Nasal liquorrhea - the outflow of cerebrospinal fluid from the cerebrospinal fluid spaces of the cranial cavity into the nasal cavity or paranasal sinuses due to the presence of a congenital or acquired defect in the bones of the skull base and meninges of various etiologies. Nasal liquorrhea leads to potentially fatal complications: meningitis, meningoencephalitis, pneumocephalus, brain abscess. Also, with nasal liquorrhea, less dangerous complications may occur: aspiration bronchopneumonia and gastritis. The article presents a case of aspiration pneumonitis in two patients with nasal liquorrhea treated at the N.N. N.N. Burdenko during the COVID-19 pandemic. Both patients noted the profuse nature of the nasal liquorrhea, complained of coughing in a horizontal position. In both cases, no RNA virus (SARS-CoV-2) was detected during the polymerase chain reaction. Antibodies (IgG, IgM) to coronavirus were not detected. Computed tomography of the chest organs in both cases revealed areas of frosted glass darkening. Since no data was obtained for coronavirus infection (negative tests for coronavirus, lack of antibodies), changes in the lungs were interpreted as a consequence of constant aspiration of cerebrospinal fluid. The patients were admitted to a separate ward. Both patients underwent endoscopic endonasal plasty of the skull base defect. The postoperative period in both cases was uneventful. In both cases, the patients underwent computed tomography scan of the chest organs one month later. On the photographs, the signs of pneumontis completely regressed.